Microstructure dependent fatigue life prediction for short fibers reinforced composites: Application to sheet molding compounds. (September 2020) - Laribi, M.A.; Tamboura, S.; Fitoussi, J.; Shirinbayan, M.; Bi, R.Tie; Tcharkhtchi, A.; Dali, H. Ben
Highlights: This paper proposes a fatigue life predictive model for SMC composites in which microstructure is an input data. A two-step selection method involving an original ultrasonic method and damage analysis is presented. The high influence of SMC microstructure on fatigue life has been demonstrated. An experimental link between monotonic loading damage and fatigue life has been emphasized. A new fatigue life predictive approach based on this intrinsic relation and a micromechanical damage model has been built. Abstract: Because of the high variability of SMC microstructure due to material flow during thermoforming, fatigue life prediction in real automotive structure represents a huge challenge. In this paper, we present a two-step microstructure selection involving an original ultrasonic method which is briefly presented. Then, on the basis of four selected microstructure configurations, an accurate experimental damage analysis is performed including both monotonic and cyclic loading. The high microstructure dependence of the obtained Whöler curves is demonstrated. Moreover, an experimental link between monotonic damage and fatigue life is emphasized. Then, a new fatigue life prediction methodology based on the later is proposed. This methodology also uses a micromechanical damage model in which a local damage criterion is involved for monotonic loading damage prediction. A very good agreement between experimental and predicted Whöler curves is demonstrated for all studied microstructures and three working temperatures. Finally, the model allows building a microstructure dependent Whöler curve abacus which may be very useful for SMC structures design.